Toll-like receptor 3 adjuvant in combination with virus-like particles elicit a humoral response against HIV. Issue 48 (21st November 2016) - Poteet, Ethan; Lewis, Phoebe; Chen, Changyi; Ho, Sam On; Do, Thai; Chiang, SuMing; Labranche, Celia; Montefiori, David; Fujii, Gary; Yao, Qizhi
Highlights: VLPs in combination with TLR3 adjuvant induce a strong humoral response. VLPs in combination with TLR3 adjuvant induced most potent neutralizing antibodies. Correlation between germinal centers and potency of neutralizing antibodies. Abstract: Human Immunodeficiency Virus (HIV) Virus-Like Particles (VLPs) composed of HIVIIIB Gag and HIVBaL gp120/gp41 envelope are a pseudovirion vaccine capable of presenting antigens in their native conformations. To enhance the immunogenicity of the HIV Env antigen, VLPs were coupled to VesiVax Conjugatable Adjuvant Lipid Vesicles (CALV) containing one of four toll-like-receptor (TLR) ligands, each activating a receptor with distinct cellular localization and downstream pathways. C57BL/6 mice were vaccinated by intranasal prime followed by two sub-cheek boosts and their sera immunoglobulin and neutralizing potency were measured over a duration of 3 months after vaccination. PBS control, VLPs alone, CALV + VLPs, and VLPs complexed with CALV and ligands for TLR2 (PAM3CAG), TLR3 (dsRNA), TLR4 (MPLA), or TLR7/8 (resiquimod) were evaluated based on antibody titer, IgG1 and IgG2c class switching, germinal center formation, T follicular cells and potency of neutralizing antibodies. Consistently, the TLR3 ligand dsRNA complexed to CALV and in combination with VLPs (CALV(dsRNA) + VLPs) induced the strongest response. CALV(dsRNA) + VLPs induced the highest titers against the recombinant vaccine antigens clade B Bal gp120 and pr55 Gag. Additionally, CALV(dsRNA) + VLPs induced cross-clade antibodies, represented by high titers of antibody to clade c 96ZM651 gp120. CALV(dsRNA) + VLPs induced predominantly IgG2c over IgG1, a response associated with T helper type 1 (Th1)-like cytokines. In turn, CALV(dsRNA) + VLP immunized mice generated the most potent neutralizing antibodies against HIV strain MN.3. Finally, at time of sacrifice, a significant increase in germinal center B cells and T follicular cells was detected in mice which received CALV(dsRNA) + VLPs compared to PBS. Our results indicate that CALV(dsRNA) is a superior adjuvant for HIV VLPs in generating a Th1-like immunoglobulin profile, while prolonging lymph node germinal centers, T follicular cells and generating neutralizing antibodies to a highly sensitive tier 1A variant of HIV.